Design, synthesis, and apoptotic antiproliferative action of new benzimidazole/1,2,3-triazole hybrids as EGFR inhibitors - Ahmed, Alshimaa A. Y.; Mohammed, Anber F.; Almarhoon, Zainab M.; Bräse, Stefan; Youssif, Bahaa G. M. (Frontiers in Chemistry, 2025)
IntroductionThis work outlines the design, synthesis, and biological evaluation of a new series of benzimidazole/1,2,3-triazole hybrids as apoptotic antiproliferative agents that inhibit the EGFR pathway.MethodsThe research assesses the antiproliferative efficacy of compounds 6a-i and 10a-i against various cancer cell lines.Results and DiscussionThe research emphasizing hybrids 6i and 10e for their remarkable activity, with GI50 values of 29 nM and 25 nM, respectively. The inhibitory effects of the most potent hybrids 6e, 6i, 10d, 10e, and 10g on EGFR were assessed. Compounds 6i and 10e exhibited greater potency than erlotinib as EGFR inhibitors. Compounds 6i and 10e were also examined for their apoptotic potential, revealing that these compounds promote apoptosis by activating caspase-3, caspase-8, and Bax, while down-regulating the anti-apoptotic protein Bcl-2. Molecular docking experiments are thoroughly examined to validate the binding interactions of the most active hybrids, 6i and 10e, with the EGFR active site. Furthermore, our new study examined the ADME properties of the new hybrids.